EVALUASI IMPLEMENTASI KEBIJAKAN STANDAR NASIONAL PERPUSTAKAAN DALAM RANGKA MENINGKATKAN KEPUASAN PEMUSTAKA STUDI KASUS PADA PERPUSTAKAAN DAERAH KABUPATEN BEKASI TAHUN 2024 – 2025 - Mardiana Tri Hidayanti; Agus Cholik (Jurnal Ilmu Administrasi Publik, 2025)
This study emphasizes the importance of implementing the National Library Standards (NLS) Policy Number 2 of 2024 as a strategic instrument to improve service quality and user satisfaction at the Bekasi Regency Public Library, considering that the NLS serves as the main guideline for fulfilling standards related to collections, services, human resources, and library facilities and infrastructure. The purpose of this study is to evaluate the implementation of the NLS policy, identify obstacles in its implementation, and formulate policy reinforcement strategies to enhance the quality of regional library services. Using a qualitative approach with a case study method, data were collected through in-depth interviews, field observations, and documentation studies. The results indicate that the implementation of the NLS policy has produced administrative and institutional achievements, as reflected by the attainment of A-level accreditation and an increase in the number of collections from 17,860 titles in 2023 to 18,414 titles in 2025. However, the percentage of target fulfillment declined from 89% to 68%, the ratio of collections to users has not met the required standard, and certified librarians are not yet available. Policy implementation also remains constrained by limited budget allocation, the lack of fully integrated digital services, weak dissemination of the 2024 NLS policy, and a bureaucratic structure that restricts flexibility in decision-making. This study recommends strengthening librarian competencies through certification and training programs, increasing budget allocation, optimizing integrated digital services, and restructuring the organizational framework to be more adaptive in order to improve the effectiveness of NLS implementation and user satisfaction.